Reply to a discussion of 'a research agenda on systems approaches to infrastructure' by david elms. Issue 4 (2nd October 2021) - Mijic, Ana; Whyte, Jennifer; Myers, Rupert; Angeloudis, Pangiotis; Cardin, Michel-Alexandre; Stettler, Marc; Ochieng, Washington
ABSTRACT: We thank Prof Elms for his insightful comments and suggestions. The paper was indeed aimed at setting the future direction for the Centre for Systems Engineering and Innovation (CSEI) at Imperial College London, with the hope that the ideas will inspire others who work in the same or similar area of research. We are pleased to see that Prof Elms enjoyed reading our paper.